Variations in gait development: what is normal and when should I be concerned?. Issue 2 (February 2022) - Douglas, Christine; Wright, Jonathan; Jacobs, Benjamin
Abstract: Normal healthy children vary in the pattern of their gait development. Deviation from parents' expectation and comparison with peers may lead to anxiety and medical consultation. It is essential to identify the important pathological diagnoses among the array of normal variants to facilitate early intervention and optimize outcomes.